Pretest-Posttest Control Group Design of Discovery Learning-Based Content Learning System in The Materials of Atomic Structure and Periodic Elements System of Class X Vocational Schools To Improve High-Level Thinking Ability - Sinta Rahmatika; Rahadian Zainul (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
A learning process in the form of electronics employing online learning and merging discovery learning learning models is known as a discovery learning-based content learning system. This study sought to determine the efficacy of a content learning method based on discovery learning for class X SMK students studying periodic systems and atomic structure material. This study employs the ADDIE development model, which is only applicable to the implementation stage and whose efficacy is being evaluated on a limited scale. Higher-order thinking abilities and student learning outcomes are impacted by the findings of measuring the efficacy of the discovery learning-based content learning system, as shown by an increase in the average score from the pretest to the posttest. The results of the t-test showed sig (2-tailed) 0.05, indicating that there is a significant difference between the learning outcomes and HOTS of students who use and don't use a content learning system based on discovery learning. This implies that content learning systems based on discovery learning on content related to atomic structure and the periodic system of elements are effectively designed to enhance student learning outcomes and higher-order thinking skills.